Novel Use of Obsidio Conformable Embolic in Thoracic Duct Embolization - Labiste, Chase; Pierre, Kevin; McCurry, Andrew; Amador, Isabella; McCann, George; Kent, Thomas; Geller, Brian; Davis, Hugh (Journal of Clinical Interventional Radiology ISVIR, 2024)
Chylothorax is a potentially serious condition resulting from thoracic duct injury. When chyle output remains high despite medical management, invasive interventions such as surgical ligation or percutaneous thoracic duct embolization (TDE) may be necessary. Obsidio is a novel conformable embolic agent that shares properties of both coil and liquid embolic agents. A 37-year-old man presented with left-sided chylothorax, refractory to medical management, following a high-speed motorcycle collision. The thoracic duct was successfully embolized using Obsidio placed between coil packs with fibered coils. This case report demonstrates the first successful use of Obsidio for TDE in a patient with traumatic chylothorax.
Keywords: thoracic duct embolization; Obsidio; chylothorax